SISTEM INFORMASI PEMASARAN PRODUK DESA BERBASIS WEB - Kartarina, Kartarina; Irfan, Pahrul; Satria, Cristofer (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
Batu Mekar Village is one of the villages in West Lombok Regency in Lingsar District. Batu Mekar village has many products in the form of handicrafts such as bags, lamp decorations made from ketak or agricultural and plantation products such as coffee, palm sugar and others. The problem that exists in Batu Mekar Village is the low sales price of handicraft products because the product is only left at a souvenir shop. The decrease in the number of sales was not due to a decrease in the number of tourists who ended up on the island of Lombok due to the earthquake. In addition, the limited promotion media. This research was developed using the Rapid Application Development method. This research resulted in an online sales information system as a medium for handicraft sales, so that the public could directly sell their products without going through intermediaries as well as promotional media so that handicraft products can be sold directly and can be recognized by the wider community. The developed application can be used as a promotional medium as well as a means of selling Batu Mekar village handicraft products.